Perancangan Sistem Pakar Penentuan Ekstrakurikuler Menggunakan Metode Forward Chaining di SMK Pembangunan Cibadak - Ian Mulyana; Muhammad Ikhsan Thohir; Anggun Fergina (G-Tech: Jurnal Teknologi Terapan, 2024)
Extracurricular is a learning process that takes place outside normal class hours, aimed at developing students' interests and talents. The problem that arises is the lack of proper mapping in choosing extracurricular activities, so that students often have difficulty choosing activities that suit their interests and talents. So an expert system application was designed to assist the extracurricular selection process using the forward chaining method. The main feature of this application is calculating and calculating this data to provide appropriate extracurricular recommendations. This application development uses the waterfall method to ensure a more structured and systematic process. testing with blackbox testing with results in accordance with the plan which shows an interactive system on all devices and the results of the analysis regarding potential interests and talents are displayed in the output.